2017
DOI: 10.21767/1791-809x.1000474
|View full text |Cite
|
Sign up to set email alerts
|

An Original Research about: The Associations of Depression and Fatigue with Quality of Life among Palestinian Patients with Cancer

Abstract: Purpose: To explore the relationships between depression, fatigue and QoL among patients diagnosed with cancer in the West Bank.Method: This was a descriptive, correlational study. 172 patients with lung, breast, colon, prostate and stomach cancer participated in the study. Depression, fatigue and quality of life were assessed for patients who undergoing chemotherapy. All instruments were reliable and valid. Results:The mean score for depression was 22 (SD=8). This indicated that many patients in this study ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Such attitudes may contribute and reinforce self-pity, self-stigma (Fominaya et al, 2016), and generate negative emotions like shame and guilt. In the same line, Deridi, Asmar, and Al-Rjou (2016) found that a significant proportion of Palestinian cancer patients from the West Bank suffered from moderate to severe depression. Female cancer patients reported higher level of depression, difficulties in social functioning (e.g.…”
Section: Paradoxical Srs Of Cancer Patientsmentioning
confidence: 86%
See 1 more Smart Citation
“…Such attitudes may contribute and reinforce self-pity, self-stigma (Fominaya et al, 2016), and generate negative emotions like shame and guilt. In the same line, Deridi, Asmar, and Al-Rjou (2016) found that a significant proportion of Palestinian cancer patients from the West Bank suffered from moderate to severe depression. Female cancer patients reported higher level of depression, difficulties in social functioning (e.g.…”
Section: Paradoxical Srs Of Cancer Patientsmentioning
confidence: 86%
“…Female cancer patients reported higher level of depression, difficulties in social functioning (e.g. changes in roles, work, social activities, relationship with partners and family, and lower quality of life compared to male cancer patients (Deridi et al., 2016). Fortunately, caregiving represents a cultural virtue in Palestinian culture based on reciprocal caregiving and a caring religion that strengthens and empowers cancer patients (Albarghouthi, 2017).…”
Section: Research Findingsmentioning
confidence: 99%
“…Furthermore cross-sectional study conducted at Beit Jala Governmental Hospital in Bethlehem and Augusta Victoria private Hospital in Jerusalem found that sons of mothers with late-stage cancer, daughters of mothers with palliative and other treatments (those who had been treated for 3-6 months), and husbands whose wives had radiotherapy treatment (especially those who lived in a village) had higher depression scores. Because of the predicted death anxiety of the sons, when coping, education of the mothers is an available intervention, and depression evaluation among family members is needed, with therapy recommended (Dreidi, Asmar, & Rjoub, 2017).…”
Section: Depression Rehabilitation Interventions and Treatments Among...mentioning
confidence: 99%
“…(Mhaidat et al, 2009) and Saudi Arabia (Almostadi, 2012). Secondly patient and family education (Dreidi et al, 2017) similarly found in the international study of (Li et al, 2016;Sui et al, 2020), thirdly the use of palliative care services for depression treatment (Elessi, 2018) supported by (Li et al, 2016;Piil et al, 2015;Sui et al, 2020). But in Palestine was no palliative care service available for cancer patients or their families, absence of organizations strategic planning for palliative care, no presence of educational resources for palliative care, no presence of communication or consultation to the religious man, absence of bereavement support group, no active follow up for the patient and the family, no standards for palliative care service or training programs in palliative care, no home care service for palliative care, absence of community awareness for palliative care And Absence of national standard for palliative care (Shawawra & Khleif, 2011).…”
Section: Depression Rehabilitation Interventions and Treatments Among...mentioning
confidence: 99%
See 1 more Smart Citation